Feiloa‘iga ma Talanoaga ma ‘āiga: Talanoa with Family in the Archives - Ieremia-Allan, Wanda (Waka Kuaka, 2023)
This paper applies the Talanoa methodology as an archival approach to historical objects. This engagement with archives departs from, or perhaps expands, Timote Vaioleti’s initial envisioning of Talanoa as an approach for research into educational and social issues confronting Pacific people in Aotearoa. This shift employs Talanoa in the context of interdisciplinary, historical, literary, Pacific studies and Indigenous studies research. In particular, I am interested in the underexamined potential of Talanoa in particular disciplinary sites and objects of study. This paper engages Talanoa as a philosophical paradigm (methodology) and a research method in the study of ancestors’ feau (messages) in the London Missionary Society (LMS) Gagana Sāmoa (Samoan language) newspaper O le Sulu Samoa (Sulu). I argue that the Sulu archival record is a palimpsest through which we can see the multiple articulations of Indigenous presence that exist within and beyond the page. Firstly, Talanoa renders these embodied memories in a feiloa‘iga ma le tālatalanoaga ma ‘āiga (meeting and gathering of family) as a contact zone, where descendants reconcile affective feelings and emotions. Secondly, as a method Talanoa produces a generative dialogical Samoan reading between texts, memory recall and oral histories. Ultimately, although conversations about Pacific research methodologies have been dominated by social science disciplines and thinkers, this paper argues that in the context of archival and historical research, Talanoa methodology can be conceived as a highly productive facilitator for embodied conversations with and between relatives that cross spatio-temporal, national, cultural, ideological, corporeal and disciplinary dimensions.